SpyTag/SpyCatcher display of influenza M2e peptide on norovirus-like particle provides stronger immunization than direct genetic fusion - Lampinen, Vili; Gröhn, Stina; Soppela, Saana; Blazevic, Vesna; Hytönen, Vesa P.; Hankaniemi, Minna M. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Virus-like particles (VLPs) are similar in size and shape to their respective viruses, but free of viral genetic material. This makes VLP-based vaccines incapable of causing infection, but still effective in mounting immune responses. Noro-VLPs consist of 180 copies of the VP1 capsid protein. The particle tolerates C-terminal fusion partners, and VP1 fused with a C-terminal SpyTag self-assembles into a VLP with SpyTag protruding from its surface, enabling conjugation of antigens via SpyCatcher. Methods To compare SpyCatcher-mediated coupling and direct peptide fusion in experimental vaccination, we genetically fused the ectodomain of influenza matrix-2 protein (M2e) directly on the C-terminus of norovirus VP1 capsid protein. VLPs decorated with SpyCatcher-M2e and VLPs with direct M2 efusion were used to immunize mice. Results and discussion We found that direct genetic fusion of M2e on noro-VLP raised few M2e antibodies in the mouse model, presumably because the short linker positions the peptide between the protruding domains of noro-VLP, limiting its accessibility. On the other hand, adding aluminum hydroxide adjuvant to the previously described SpyCatcher-M2e-decorated noro-VLP vaccine gave a strong response against M2e. Surprisingly, simple SpyCatcher-fused M2e without VLP display also functioned as a potent immunogen, which suggests that the commonly used protein linker SpyCatcher-SpyTag may serve a second role as an activator of the immune system in vaccine preparations. Based on the measured anti-M2e antibodies and cellular responses, both SpyCatcher-M2e as well as M2e presented on the noro-VLP via SpyTag/Catcher show potential for the development of universal influenza vaccines.